Analisis Kinerja Dan Konsumsi Sumber Daya Aplikasi Web Server Pada Platform Raspberry Pi - Andhika Dwitama Putra; Widhi Yahya; Adhitya Bhawiyuga (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Nowadays, the utilization of single board computer in the current digitalitation era is developing rapidly. One example of Single Board Computer is Raspberry Pi. The limited hardware specification makes the resource allocation consumed by Raspberry Pi also limited. Web server application has a role in affecting resources performance and consumption in the Raspberry Pi platform. This research aims to figure out which web server that has a good resources performance and consumption in Raspberry Pi. The test method done includes the resources performance and consumption test by using several parameters: throughput, average response time, cpu and memory power usage, while the web server application compared including Apache, Nginx, Lighttpd, Apache Tomcat, and Jetty. The test is using user as an input parameter in the amount of 250, 500, 1000 and 1200. Based on the test result as well as the analysis, Nginx have the best performance based on the highest score of throughput with 357 KB/s and the lowest score of average response time with 1117 ms in serving 1200 user and using data to the test in the amount of 1.536,1 Kbytes and Lighttpd have the best resources consumption based on the lowest score of cpu usage with 4,46 % and the lowest score of memory usage with 22,16 % in serving 1200 user and using data to the test in the amount of 1.019,1 Kbytes.